Private provision of a complementary public good - Richard Schmidtke (Center for Economic Studies and ifo Institute (CESifo), 2006)
For several years, an increasing number of firms have been investing in Open Source Software (OSS). While improvements in such a non-excludable public good cannot be appropriated, companies can benefit indirectly in a complementary proprietary segment. We study this incentive for investment in OSS. In particular we ask how (1) market entry and (2) public investments in the public good affect the firms' production and profits. Surprisingly, we find that there exist cases where incumbents benefit from market entry. Moreover, we show the counter-intuitive result that public spending does not necessarily lead to a decreasing voluntary private contribution.
Keywords: C72; L13; L86; 330